Nonlinear numerical analysis and averaging method applied atomic force microscopy with viscoelastic term - Ribeiro, Mauricio A.; Kurina, Galina A.; Tusset, Angelo M.; Balthazar, Jose M. [UNESP] (Springer Nature, 2022)
We investigated the nonlinear behavior of an atomic force microscopy system with the contribution of the medium viscoelasticity term. Atomic force microscopy is one of the most used techniques for analyzing the surface topology of samples of interest. We propose a mathematical model for the nonlinear dynamics of the probe and we also assign a term that describes the viscoelasticity of the medium in which the probe is inserted. For our numerical analysis of nonlinear dynamics, we used the Lyapunov Exponent, Bifurcation Diagram, phase maps and Poincaré maps. We also determine a solution for a set of parameters using perturbation theory. In this paper, it is also shown that using higher approximations of averaging method, which allows to solve systems of differential equations with slowly changing variables instead systems with fast change of variables, is very effective to study dynamics of an atomic force microscopy.
Keywords: Atomic force microscopy; Averaging method; Nonlinear dynamics